2013
DOI: 10.1103/physrevlett.110.032502
|View full text |Cite
|
Sign up to set email alerts
|

Isγ-Ray Emission from Novae Affected by Interference Effects in theF18(p,α)

Abstract: The 18 F(p,α) 15 O reaction rate is crucial for constraining model predictions of the γ-ray observable radioisotope 18 F produced in novae. The determination of this rate is challenging due to particular features of the level scheme of the compound nucleus, 19 Ne, which result in interference effects potentially playing a significant role. The dominant uncertainty in this rate arises from interference between J π =3/2 + states near the proton threshold (Sp = 6.411 MeV) and a broad J π =3/2 + state at 665 keV a… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
55
2

Year Published

2013
2013
2017
2017

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 39 publications
(61 citation statements)
references
References 29 publications
4
55
2
Order By: Relevance
“…A good agreement shows up, within the experimental uncertainties. The observed levels, correspond to levels in 19 Ne which are reported in Table 1, taken from [35] or [9]. Although the energy resolution is poorer than in the previous run (mainly due to the poorer angular resolution of the present experimental apparatus), the agreement between the two data sets confirms once again the applicability of the THM to the present reaction.…”
Section: Resultssupporting
confidence: 71%
See 2 more Smart Citations
“…A good agreement shows up, within the experimental uncertainties. The observed levels, correspond to levels in 19 Ne which are reported in Table 1, taken from [35] or [9]. Although the energy resolution is poorer than in the previous run (mainly due to the poorer angular resolution of the present experimental apparatus), the agreement between the two data sets confirms once again the applicability of the THM to the present reaction.…”
Section: Resultssupporting
confidence: 71%
“…Direct data from [5,6] are reported for comparison and normalization purposes. In the lower panel the full dots represents the results for a J π =5/2 − assumption for the same level as discussed in [9]. This uncertainty leads therefore to an uncertainty between the S(E) lower limit (corresponding to J π =5/2 − for the 6460 keV state in Figure 2.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A Γ p of 7.3±0.6 eV was extracted from proton transfer data [10], however, the population of the 330 keV resonance could have been contaminated by nearby states. 19 Ne studies by Laird et al [17] and Bardayan et al [18], respectively, found discrepancies in the spin and parity assignments for levels close to the proton threshold in 19 Ne. This may have ramifications for the 18 F(p,γ) 19 Ne reaction rate at nova temperatures; the new spin and parity assignments differ from those published previously, leading to changes in the interference effects with stronger, higher lying states, hence altering the capture cross section.…”
Section: Thementioning
confidence: 99%
“…This points to the need of further major advances in many-body methods to access a wider range of nuclei and experimental observables, while retaining the predictive power of ab initio methods, which makes them suitable for e.g. targeting short-lived nuclei that are inaccessible by experiment but essential to further modeling, for example, of the dynamics of X-ray bursts and the path of nucleosynthesis (see, e.g., [13,14]). …”
mentioning
confidence: 99%